PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE ( TPS ) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV A SDN 30 PINGGIR - Sri Lestari; Erlisnawati Erlisnawati; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research was sains studies students achievement in fourth graderes (IVA) SDN 30 Pinggir still low with average value 60,25 (with KKM 70). The purpose of this research was to improve the student achievment of the fourth graderes (IVA) SDN 30 Pinggir with the Implementation of Cooperative Learning Type Think Pair Share (TPS). This research was an classroom action research with two cycles in second semester 2014/2015. Before implementation of Cooperative Learning Type Think Pair Share average 60,25, after implementation of Cooperative Learning Type Think Pair Share, UH I was 67,00 that improve 11,20% frombefore exam with average 60,25. UH II was 73,00 that improve 21,16%. Teacher’s activities with the implementation of Cooperative Learning Type Think Pair Share at first meeting of first cycle was 70,8% (good category), and second meeting was 79,1% (good category) that improve 8 point. At second cycle, teacher’s activities at first meeting was 87,5% (good category) that improve 9 point from second meeting of first cycle. Second meeting of second cycle was 91% (verygood category) which improve 4 point. Student activities at first meeting of first cycle was 62,5% (enough category), and second meeting 66,6% (enough category) that impropve 5 point. At second cycle, students activities at first meeting was 79,1% (good category) that improve 12 point from second meeting of first cycle. Second meeting of second cycle was 87,5% (verygood category) which improve 8 point. Implementation of Cooperative Learning Type Think Pair Share can improved sains studies atudent achievment of fourth graderes (IVA) SDN 30 Pinggir.Key Words : Cooperative Learning Type TPS, Sains Studies’s Achievment